2020
DOI: 10.1126/sciadv.aay9344
|View full text |Cite
|
Sign up to set email alerts
|

There is no liberal media bias in which news stories political journalists choose to cover

Abstract: Is the media biased against conservatives? Although a dominant majority of journalists identify as liberals/Democrats and many Americans and public officials frequently decry supposedly high and increasing levels of media bias, little compelling evidence exists as to (i) the ideological or partisan leanings of the many journalists who fail to answer surveys and/or identify as independents and (ii) whether journalists’ political leanings bleed into the choice of which stories to cover that Americans ultimately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Conservatives are more often fooled by bots purporting to share their ideology than liberals (21). Some scholars also contend that established news organizations, which are an influential source of factually accurate information, favor news coverage promoting liberal values, although this characterization is disputed (31)(32)(33). In such an environment, symmetrical motivations to believe claims reinforcing a preferred worldview would promote both liberal accuracy and conservative inaccuracy.…”
Section: Theorymentioning
confidence: 99%
“…Conservatives are more often fooled by bots purporting to share their ideology than liberals (21). Some scholars also contend that established news organizations, which are an influential source of factually accurate information, favor news coverage promoting liberal values, although this characterization is disputed (31)(32)(33). In such an environment, symmetrical motivations to believe claims reinforcing a preferred worldview would promote both liberal accuracy and conservative inaccuracy.…”
Section: Theorymentioning
confidence: 99%
“…This kind of bias has been termed gatekeeping or selectivity in the previous literature [22] . Although note that a recent US study found no evidence of a liberal bias in which news stories political journalists choose to cover [6] 1 .…”
Section: Data Collection and Initial Codingmentioning
confidence: 94%
“…We chose the weighted mean and median as our estimators. 6 Figure 9 shows the results for the logRR metric.…”
Section: Ideology Tagsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis, published in 2000, of 59 quantitative studies concluded that negligible bias existed in news coverage of presidential election campaigns since 1948 [ 8 ]. While accusations of bias in the news, fueled by an extremely polarized political climate, seem to have increased in recent years, a paper published in 2020 again found no evidence of liberal bias in political news coverage [ 9 ].…”
Section: Introductionmentioning
confidence: 99%